Hubungan Penggunaan Gadget Dan Indeks Masa Tubuh Dengan Kualitas Tidur Pada Remaja Di Masa Pandemi Covid-19 Di MTS Salafiyah Depok Tahun 2020 : The Relationship between Gadget Use and Body Mass Index with Sleep Quality in Adolescents During the Covid-19 Pandemic At MTS Salafiyah Depok in 2020 - Serly Malinda Putri (Dohara POAJ, 2021)
Introduction: in adolescence, adolescents must be able to meet their physiological needs, one of which is the need for rest and sleep. Sleep patterns in adolescence usually have different sleep patterns because adolescents experience many changes that make adolescents reduce their sleep time. Coupled with the covid-19 pandemic, teenagers become anxious, making them experience fewer obstacles to social interaction. The covid-19 pandemic has also made schools and institutions replace online learning methods using gadgets. So that this can make adolescents more intense in using gadgets and this behavior can affect the quality of adolescent sleep. Apart from the use of nutritional gadgets, it can also be a factor that affects sleep quality. Methods: The research method used is a correlational method with a cross-sectional approach. The population used in this study were teenagers aged 13-15 years in MTS Salafiyah. The sample in this study was 67 respondents. The sampling technique used was purposive sampling. Data collection was done by filling out questionnaires and observation sheets that were already on the google form link. Results: Most of the respondents were 13 years old as many as 36 respondents (53.7%). female sex as many as 46 respondents (68.7%). the characteristics of respondents based on the type of activity carried out the most are those who access social media with a total of 46 people (68.7%). Spearman rank shows the value of using gadgets with a sleep quality of p = 0.012. While the body mass index value with sleep quality with a p-value = 0.038. Discussion: There is a relationship between the use of gadgets with sleep quality and body mass index with sleep quality in adolescents during the covid-19 pandemic at MTS Salafiyah Depok in 2020.